2021
DOI: 10.1186/s13643-021-01577-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence adherence to surgical antimicrobial prophylaxis (SAP) guidelines: a systematic review

Abstract: Background Despite the extensive research that has been conducted to date, practice often differs from established guidelines and will vary between individuals and organisations. It has been noted that the global uptake of local and international surgical antimicrobial prophylaxis (SAP) guidelines is poor with limited research investigating factors that affect guideline adherence. The purpose of this systematic review was to determine the reported barriers and enablers to the adherence of SAP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 101 publications
1
20
0
2
Order By: Relevance
“…Others have also reported that physicians may prescribe antibiotics due to fear of infection-related complications [ 57 , 59 ]. Fear of repercussions could drive overuse while prescribing antibiotics provides comfort and alleviates perceived risk [ 61 ]. Finally, a related review of factors influencing adherence to guidelines on surgical antibiotic prophylaxis identified that provider training, personal experience and supervisors’ opinions may be stronger influencers on behaviour than clinical guidelines themselves [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported that physicians may prescribe antibiotics due to fear of infection-related complications [ 57 , 59 ]. Fear of repercussions could drive overuse while prescribing antibiotics provides comfort and alleviates perceived risk [ 61 ]. Finally, a related review of factors influencing adherence to guidelines on surgical antibiotic prophylaxis identified that provider training, personal experience and supervisors’ opinions may be stronger influencers on behaviour than clinical guidelines themselves [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existen estudios que evalúan la adherencia de los cirujanos a las guías de manejo en relación con la práctica quirúrgica (26); incluso se reportan de cada cirujano en el manejo quirúrgico para el cáncer de colon obstructivo en neoplasias de colon derecho, transverso, izquierdo, sigmoides y unión rectosigmoidea. Este formulario solo se podía diligenciar una vez, sin condicionar el número de instituciones en las que laborara el participante.…”
Section: Pronóstico Y Supervivenciaunclassified
“…1 However, lack of adherence to follow protocol for SAP is among one of the factors for irrational use. 6,7 Bacteria that become resistant to multiple antibiotics are often the result of incorrect or prolonged antibiotic use. 8 30% to 50% of antibiotics prescribed in hospitals are for postsurgical prophylaxis, and almost 30% to 90% of these regimens are unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…These can be in the form of incorrect timing and duration of the prophylactic therapy. 6,10 Surgical antimicrobial prophylaxis lacks sufficient information and recommendations in India; hence there is an unmet need to collect baseline data. The purpose of this study was to examine the trend in the prescription of antimicrobial prophylaxis in various surgical specialties and apply the recommended SAP in a selected unit of surgery, and observe the outcomes of patients in that unit.…”
Section: Introductionmentioning
confidence: 99%